STUDENTS' CRITICAL THINKING SKILLS IN SOLVING PISA-TYPE MATH PROBLEMS IN THE CONTEXT OF FERRIS WHEELS - Pratiwi Lidia; Zulkardi (Journal of Pedagogical Content Knowledge, 2025)
This study aims to describe students' critical thinking skills in solving PISA-type mathematics problems in the context of the Ferris wheel at SMP IT Izzuddin Palembang. This study is a descriptive study with a qualitative approach and was carried out face-to-face, with the subjects of the study being 22 students of class VIII. 2 Halimah SMP IT Izzuddin Palembang. Data collection techniques used written tests and interviews. Based on the results of the analysis and discussion that have been carried out, students' critical thinking skills are in the low category with an average score of 40.54. Based on the percentage of achievement of critical thinking ability indicators, there are several indicators that often appear, namely the analysis indicator 68% and the indicator that appears the least is the inference indicator 4%.